The Effectiveness of a Counseling Program Based on Adlerian Approach in Improving Self-Disclosure and Conflict Management Among a Sample of Engaged Male Teachers in Zarqa District - Al-Khazaleh, Ziad; Bani Younes, Mohammad (Jordan Journal of Educational Sciences, 2017)
The study aimed to identify the effectiveness of a counseling program based on the Adler theory in improving self-disclosure and conflict management among a sample of engaged male teachers at schools that belong to: Zarqa Governorate, Educational Zarqa First Directorate, Educational Zarqa Second Directorate, and Educational Roseifa Directorate. The study sample consisted of (30) engaged male teachers. The sample was distributed equally into (15) teachers who represented the experimental group, and (15) teachers who represented the control group. In order to achieve the study aims, the scales of the self-disclosure, conflict management, and a counseling program were constructed based on the Adlerian approach. The program consisted of (14) sessions. After testing the psychometric characteristics of the study tools, the study was applied on the sample individuals. The results revealed statistically significant differences between the individuals of both groups in improving self-disclosure and conflict management in favor of the experimental group. Moreover, after implementing the follow up scale beyond a one month period, the study showed that the experimental group retained the effect of the program